Legal Protection of Talunombo Written Batik Wonosobo in Perspective Anthropology Law - Emy Handayani; Suparno Suparno (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Legal protection for the creation of Talunombo Wonosobo batik motives is to preserve the traditional written batik owned by Talunombo batik craftsmen in the study of Legal Anthropology approaches, both comparative and empirical approaches. The comparative approach references to the rules made to protect the creation of the Talunombo Sapuran Wonosobo batik motif based on the Copyright Law Numb. 19 Years 2022. empirical approach looks at the reality that occurs in the community of Talunombo batik craftsmen who love the products they made to preserve the nation's cultural heritage. The suggestion used should be that the Wonosobo Regional Government can synergize to be able to provide legal protection to the existence of written batik craftsmen by protecting the talunombo handwritten batik products in the  rapid economic development so that they do not become heredity and can be preserved as batik icons that can prosper the Talunombo handwritten batik craftsmen Sapuran Wonosobo.